EVALUASI HASIL IMPLEMENTASI THE COORDINATED MEKONG MINISTERIAL INITIATIVE AGAINST TRAFFICKING SUB-REGIONAL PLAN OF ACTION (COMMIT SPA) DALAM MENANGANI HUMAN TRAFFICKING DI THAILAND PERIODE 2011-2013 - Rahmahwati, Isti Nur; Windiani, Reni; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Thailand, Laos, Myanmar, China, Vietnam, and Cambodia createdCOMMIT and COMMIT SPA. During COMMIT SPAimplementation period 2011-2013, the number of human traffickingincreased in Thailand. Most of human trafficking victims in Thailandare exploited into sexual exploitation and forced labor. The studyaims to analyze causes of human trafficking increased duringCOMMIT SPA implementation. The study result is the increase ofhuman trafficking is caused by Thailand’s interests by using sextrafficking victims in prostitution and sex tourism activities as a drawfor foreign tourists to Thailand and labor trafficking victims inproducing prawns for supermarkets in US and European countries toget economic benefits.